Pendidikan Inklusif Gender: Analisis Pemikiran RA Kartini - Azizah, Khoridatul; Rosyida, Nailur (PSGA Institut Agama Islam Tarbiyatut Tholabah, 2024)
In the social life of Muslim societies, there are gender inequalities that contradict Islamic teachings that prioritise equality between men and women. This inequality is often justified by incorrect religious interpretations, so cultural and structural changes are needed to change the view of Islamic education to achieve gender equality. Gender education has the goal of creating justice and harmony between different types of individuals, based on the disparities that exist between them. This research is intended to investigate the concept of education that considers gender differences and the extent to which it is relevant to the goals of Islamic education. The research method uses qualitative analysis with a literature approach, involving the collection of various documents such as books, articles, journals, and other documents. The research data sources consist of main data and supporting data. The findings of this research indicate that there are conceptual similarities between gender-inclusive education and the goals of Islamic education, especially in terms of education that is mandatory for both men and women and emphasis on moral development. Through this education, it is expected that men and women can work together for the progress of the nation, in accordance with the thoughts of RA Kartini.